Bernard Stiegler, pensador do humano e da tecnologia - Pinto Neto, Moysés (DoisPontos, 2015)
resumo: Este artigo é uma introdução geral ao pensamento de Bernard Stiegler em torno da relação entre técnica e humano. Stiegler desconstroi a tradição filosófica que costumava separar technê e episteme com um enfoque histórico e materialista, a fim de provar como é impossível pensar a humanidade sem a técnica. Portanto, a relação não é de oposição, como a tradicional metafísica do espírito defende, mas composição, do modo como defendem Gilbert Simondon, Jacques Derrida, Andre Leroi-Gourhan e Gilles Deleuze. abstract: This paper is a general introduction to Bernard Stiegler’s thinking about the relation between technique and human. Stiegler deconstructs the philosophical tradition that used to separate teckhnê and episteme with a historical and materialist approach in order to prove how it is impossible to think humanity without technique. Therefore, the relation is not one of opposition, like the traditional metaphysics of spirit defends, but one of composition, as thinkers like Gilbert Simondon, Jacques Derrida, Andre Leroi-Gourhan and Gilles Deleuze defend.